2019
DOI: 10.1080/15592324.2019.1666657
|View full text |Cite
|
Sign up to set email alerts
|

PAMP-induced peptide 1 cooperates with salicylic acid to regulate stomatal immunity in Arabidopsis thaliana

Abstract: Various pathogenic species are capable of penetrating plant leaves through stomata on the leaf surface for propagation by absorbing nutrients in plant interiors. Plants have evolved abilities to close stomata to restrict pathogen infections. The model plant Arabidopsis (Arabidopsis thaliana) closes stomata when FLAGELLIN SENSING2 (FLS2), a receptor protein localized in the plasma membrane (PM) of stomatal guard cells, detects flagellin, a pathogen-associated molecular pattern (PAMP) derived from the bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…RLK7 belongs to the category XI of RLKs and acts as a receptor for PIP1 secreted peptide. Elevated expression of PIP1 has been described in Arabidopsis guard cells during Pseudomonas -induced PTI, and thus the peptide plays a role in stomatal immunity [ 72 ]. Moreover, RLK7 also contributes to Arabidopsis resistance to B. cinerea [ 73 ] and Phytium irregulare [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…RLK7 belongs to the category XI of RLKs and acts as a receptor for PIP1 secreted peptide. Elevated expression of PIP1 has been described in Arabidopsis guard cells during Pseudomonas -induced PTI, and thus the peptide plays a role in stomatal immunity [ 72 ]. Moreover, RLK7 also contributes to Arabidopsis resistance to B. cinerea [ 73 ] and Phytium irregulare [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research has shown that PIP1-induced stomatal closure is RLK7 dependent ( Hou et al, 2019 ). To explore the mechanism of PIP1-RLK7 pathway in the regulation of stomatal response, we also conducted patch clamp whole-cell recordings of S-type anion currents in Col-0 and rlk7 guard cell protoplasts under control condition and treated with 10 µM PIP1.…”
Section: Resultsmentioning
confidence: 99%
“…We used two wild type ecotypes of A. thaliana in this study: Columbia-0 (Col-0) and Landsberg-0 (Ler-0). Col-0 was the background of PIP1 over-expression lines (PIP1-OE and PIP1-OE2), and mutants rlk7 ( rlk7-2 , SALK_083114) ( Hou et al, 2019 ), bak1 ( bak1-4 , SALK_116202) ( Hou et al, 2014 ), bik1 ( Zhang et al, 2010 ; Hou et al, 2014 ), mpk3/mpk6 (SALK_151594/SALK_073907) ( Xu et al, 2014 ; Zhang et al, 2019 ), slac1-1 , slac1-3 , and rbohD/F (CS9558) ( Shen et al, 2017 ). But ost1-1 and ost1-2 were Ler-0 ecotype background.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RLK7 belongs to category XI of RLKs and acts as a receptor for PIP1 secreted peptide. Elevated expression of PIP1 has been described in Arabidopsis guard cells during Pseudomonas-induced PTI, and thus the peptide plays a role in stomatal immunity [60]. Moreover, RLK7 also contributes to Arabidopsis resistance to B. cinerea [61] and Phytium irregulare [62].…”
Section: Defense-related Genes Are Activated Also In Susceptible Intementioning
confidence: 99%